Untargeted metabolomic profiling of urine in Wistar rats reveals enhanced bioavailability of soy isoflavones post short-term consumption of noni (Morinda citrifolia) juice - Fallas Ramírez, José Manuel (2018)
Microfiltered noni (Morinda citrifolia) juice was given by cannulation to 6 Wistar rats for 13 days; the rats were also fed on a standard food formulation containing whole soy bean flour. Twenty-four hour urine was collected before and after the nutritional intervention and was analyzed by UPLC-DAD/ESI+-QTof/MS to perform an untargeted metabolomics study. A supervised multivariate OSC-PLS-DA analysis was performed to discriminate between urine samples. Among the top 10 most discriminant ions, 8 compounds were tentatively identified. Six were significantly increased after noni juice ingestion: the glucuronidate form of S-(-) equol, daidzein, 2 isomers of dihydroxyquinoline, naphthyl and hippuric acid. On the contrary, the urinary excretion of the oligosaccharides stachyose and raffinose, was significantly reduced. Still highly statistically significant, glucuronated genistein and glycetein were also elevated in urine after noni juice ingestion. Noni juice appeared to considerably enhance the bioavailability of soy isoflavone and modify the metabolism of soy oligosaccharides.